Ultrasound-guided sacral multifidus plane block versus caudal epidural block for postoperative analgesia in pediatric hypospadias surgery: A randomized double-blind controlled trial - Amr Sobhy; Radwa Tarek Mohamed; Gihan seif; Manal mohamed kamal shams; Adham Magdy Haggag; Abd El-Aziz A. Abd EL-Aziz (PLoS ONE, 2026)
Introduction Hypospadias repair is associated with moderate to severe postoperative pain in children. Caudal epidural block is traditionally considered the standard regional anesthetic technique for sub-umbilical pediatric surgeries; however, its duration of analgesia and potential adverse effects may be limited. The sacral multifidus plane block (SMPB) is a novel ultrasound-guided fascial plane technique that may provide prolonged analgesia with fewer complications. The aim of this study is to compare the analgesic efficacy and safety of ultrasound-guided sacral multifidus plane block versus caudal epidural block in children undergoing hypospadias repair. Materials and methods This prospective, randomized, double-blind controlled trial included 30 children aged 1–5 years (ASA I–II) scheduled for hypospadias repair. Patients were randomly allocated to receive either SMPB (n = 15) or caudal block (n = 15), using 1 mL/kg of 0.25% bupivacaine. The primary outcome was time to first rescue analgesia. Secondary outcomes included postoperative FLACC pain scores, total rescue analgesic consumption, intraoperative fentanyl requirements, hemodynamic variables, and block-related complications. Pain was assessed for 24 hours postoperatively. Results Demographic and intraoperative characteristics were comparable between groups. Time to first rescue analgesia was significantly longer in the SMPB group compared with the caudal group (14.8 ± 3.6 vs 9.3 ± 4.2 hours, p = 0.004). FLACC scores were significantly lower in the SMPB group at 6 and 12 hours postoperatively (p = 0.019 and p = 0.001, respectively). Total diclofenac consumption was lower in the SMPB group (0.40 ± 0.20 mg/kg vs 0.70 ± 0.24 mg/kg, p = 0.010). Intraoperative fentanyl requirements and hemodynamic parameters were similar. No major complications were observed. Conclusion Ultrasound-guided sacral multifidus plane block provides longer-lasting postoperative analgesia and reduces rescue analgesic requirements compared with caudal epidural block in pediatric hypospadias surgery, with a comparable safety profile. SMPB may represent a reliable alternative to caudal block for postoperative pain management in this population.